El sistema abreviado y su inconstitucionalidad en la vulneración de los derechos del procesado en el art. 635 numeral 3 del código orgánico integral penal - Jiménez Gallegos, Ítalo Alejandro (2017)
The Constitution of the Republic of Ecuador was approved on 28 September 2008 through a legal process unprecedented in the history of our country, in which citizens came massively to the polls to express their opinion in regards to the new constitutional text. With this new regulatory body, the Ecuadorian State has made a significant leap in which make constitutional, to consider our country as a constitutional state of law and justice, system essential for the new legal era we live in Latin American and national. In the Ecuadorian criminal legislation has evolved towards the implementation of an oral accusatory criminal proceedings, whose purpose is to engage the contradiction between the parties to the dispute within the framework of due process that recognized and guaranteed by the Constitution, however there are still legal lags with which intends to violate the rights of those investigated or prosecuted. The abbreviated procedure, mainly for its application, in accordance with determined in section 635 of the organic code Integral criminal processing must assume the Commission of an offence, i.e. plead guilty and responsible for having transgressed the criminal law and be tried quickly "Article 77 paragraph 7 literal c-"No one can be forced to testify against himself, on issues that may lead to criminal responsibility" The Constitution guarantees to all Ecuadorians that they can not be forced to testify against themselves when it involves criminal liability, by which the abbreviated procedure would be in its paragraph 2 inapplicable and unconstitutional, therefore this thesis work to analyze both constitutionally and criminal charges against this particular to the criminal process is fair equitable and may lead to a correct application of Justice in our country. Hence the need to amend Art.635 of the Comprehensive Criminal Organic Code, in order to guarantee the constitutional principles of simplification, uniformity, efficacy, immediacy, speed and procedural economy, in respect of the rights of the accused, without being one of The requirements for the abbreviated procedure to be based on self-incrimination or acceptance of the crime committed